The Effect of Utilization of Information Technology and Competence of Human Resources on The Effectiveness of Accounting Information Systems - Nurul Fitriyani Fatimah (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
The development of the business world that has entered the era of globalization requires companies to increase the effectiveness of their resourcess. Including accounting information systems. Factors that can affect the effectiveness of aacounting information systems are the utilization of information technology and the competence of human resources. This research aims to determine the effect of utilization of information technology and competence of human resouces on the effectiveness of accounting information systems on the Regional Financial and Asset Management Agency of Sumedang Regency. The method used in this research is a quantitative quantitative method with a descriptive and verification approach. Analisys of the data used in this research is multiple linear regression analisys. The collected data was processed using the Software Statistical Program For Science (SPSS) version 25 for windows. The results of this research indicate that the utilization of information technology and competence of human resources has a positive and significant effect on the effectiveness of accounting information systems either partially or simultaneously.